Improving the utilization of soybean hulls by cattle with digestive enzyme and dietary buffer supplementation - Löest, C.A.; Tigemeyer, E.C.; Johnson, B.J.; Trater, A.M.; Lambert, B.D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four ruminally cannulated Holstein steers (749 lb) were used in a 4 × 4 Latin square experiment to evaluate the benefits of supplementing digestive enzymes and dietary buffers to a soybean hull-based diet fed to steers once daily at 15.4 lb/day (as fed basis). Treatments were arranged as a 2 × 2 factorial with factors being two levels (0 and 3 grams/day) of digestive enzymes and two levels (0 and 93 grams/day) of dietary buffers. Buffers and enzymes were thoroughly mixed with the soybean hull-based diet to provide a completely mixed ration. Digestive enzyme or buffer supplementation increased (P≤0.06) diet digestibilities of dry matter, organic matter, neutral detergent fiber, and acid detergent fiber. Addition of buffer also increased (P≤0.06) digestibilities of glucose, mannose, arabinose, xylose and galactose, whereas enzyme supplementation increased (P=0.03) xylose digestibilities and tended to increase (P=0.10) arabinose digestibilities. The addition of enzymes and buffer to the soybean hull-based diet did not alter passage of liquid or solids from the rumen and therefore cannot account for any of the responses in digestion. Also, ruminal pH was not altered when steers were supplemented with digestive enzyme and(or) buffer. The lack of response in pH to buffer was surprising, because the observed effect of buffer on fiber digestibilities would have been expected to be a result of a moderation of the ruminal pH. Results from this experiment demonstrated that both digestive enzyme and buffer supplementation improved the digestibility of soybean hull-based diet, and responses were greatest when both additives were supplemented together.
Keywords: Beef; Soybean hulls; Digestive enzyme; Dietary buffer supplementation